Impact of US Financial Crisis on GDP of BRICS Economies: An Analysis Using Panel Data Approach. Issue 2 (April 2018) - Arora, Ashima; Kalsie, Anjala
The objective of the article is to analyse the impact of US financial crisis of 2008–2009 on the GDP of India and GDP of BRICS nations for the non-crisis and crisis period. Fixed effects panel data, fixed effect model, random effect model, Hausman test besides ADF unit root test were used to fulfil the abovementioned objective for the period 2000–2013. The findings displayed final consumption expenditure (FCE) to be the most influential variable in affecting the economic growth universally in both the models of India and BRICS. It was the export which was unearthed to have a more significant influence on economic growth of BRICS as a bloc followed by gross capital formation (GCF) than the other way round as in the case of India. Similarly, there was a variation in the influence of economic growth of USA when assessed separately on India in solitude and India as a part of BRICS economic bloc. This result thereby established the contagion flow of US financial crisis into the developing economies of the world.